Microbiome Heritability and Its Role in Adaptation of Hosts to Novel Resources - Bisschop, Karen; Kortenbosch, Hylke H.; van Eldijk, Timo J. B.; Mallon, Cyrus A.; Salles, Joana F.; Bonte, Dries; Etienne, Rampal S. (Frontiers in Microbiology, 2022)
Microbiomes are involved in most vital processes, such as immune response, detoxification, and digestion and are thereby elementary to organismal functioning and ultimately the host’s fitness. In turn, the microbiome may be influenced by the host and by the host’s environment. To understand microbiome dynamics during the process of adaptation to new resources, we performed an evolutionary experiment with the two-spotted spider mite, Tetranychus urticae. We generated genetically depleted strains of the two-spotted spider mite and reared them on their ancestral host plant and two novel host plants for approximately 12 generations. The use of genetically depleted strains reduced the magnitude of genetic adaptation of the spider mite host to the new resource and, hence, allowed for better detection of signals of adaptation via the microbiome. During the course of adaptation, we tested spider mite performance (number of eggs laid and longevity) and characterized the bacterial component of its microbiome (16S rRNA gene sequencing) to determine: (1) whether the bacterial communities were shaped by mite ancestry or plant environment and (2) whether the spider mites’ performance and microbiome composition were related. We found that spider mite performance on the novel host plants was clearly correlated with microbiome composition. Because our results show that only little of the total variation in the microbiome can be explained by the properties of the host (spider mite) and the environment (plant species) we studied, we argue that the bacterial community within hosts could be valuable for understanding a species’ performance on multiple resources.